The Use of Various Natural Fertilizers in the Cultivation of Chlorella sp. - Yuli Andriani; Derin Farhatu Shiyam; Zahidah Hasan; Fittrie Mellyanawatie Pratiwy (University of Prof. Dr. Hazairin, SH, 2023)
Chlorella sp. is one of the important species in the aquatic food chain and has a role in aquaculture as an alternative source of protein in feed to fulfill aquaculture activities. The use of natural fertilizers as a culture medium can use fertilizers such as POC lemna, POC vermicompost, turi putih leaf fertilizer, POC water hyacinth, bioslurry, booster manstap and extra bean sprouts. The purpose of this study is to determine the use of natural materials as fertilizer in the cultivation of Chlorella sp. which can be used as an alternative to commercial fertilizers. The method used is the study of literature. The results obtained are the use of fertilizers from natural ingredients in the cultivation of Chlorella sp. such as the use of POC lemna as much as 5% can increase the productivity of Chlorella vulgaris biomass, besides that the use of turi putih leaf fertilizer as much as 4 ml/L can increase the population of Chlorella sp., the average population increase occurs on days 6-11, the use of natural fertilizers as culture media Chlorella sp. can be an alternative and a recommendation for cultivators to cultivate natural food Chlorella sp.. In addition to the low price, the ingredients are easy to obtain by utilizing local materials, and the nutritional content contained in natural fertilizer ingredients is suitable for the needs of Chlorella sp. cultivation.